Medical Imaging 2010: Visualization, Image-Guided Procedures, and Modeling 2010
DOI: 10.1117/12.844186
|View full text |Cite
|
Sign up to set email alerts
|

Fast automatic path proposal computation for hepatic needle placement

Abstract: Percutaneous image-guided interventions, such as radiofrequency ablation (RFA), biopsy, seed implantation, and several types of drainage, employ needle shaped instruments which have to be inserted into the patient's body. Precise planning of needle placement is a key to a successful intervention. The planning of the access path has to be carried out with respect to a variety of criteria for all possible trajectories to the selected target. Since the planning is performed in 2D slices, it demands considerable e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 0 publications
0
27
0
1
Order By: Relevance
“…In fact, integration of such constraints was also proposed by the radiologists that used the system. Similar approaches from Villard and Baegert 17 or Schumann et al 18 also concentrate on the computation of suitable insertion trajectories but still depend on an appropriate weighting of the different constraints to achieve the desired planning result. Utilizing a pareto-based optimization, our approach is able to propose insertion trajectories without needing weights.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In fact, integration of such constraints was also proposed by the radiologists that used the system. Similar approaches from Villard and Baegert 17 or Schumann et al 18 also concentrate on the computation of suitable insertion trajectories but still depend on an appropriate weighting of the different constraints to achieve the desired planning result. Utilizing a pareto-based optimization, our approach is able to propose insertion trajectories without needing weights.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, another planning approach has been proposed by Schumann et al 18 where, as in Villard and Baegert, a set of constraints is used to determine the suitable insertion trajectories. The authors use a method independent of the mesh representation of the critical structures by generating socalled constraint maps for each restriction by computing a cylindrical projection with the center at the target point.…”
Section: Introductionmentioning
confidence: 99%
“…References [7][8][9][10][11][12][13][14] presented visualization methods to display puncture pathways in optimal views and better interactive methods to make it easier for surgeons to observe and adjust the planned puncture routes. References [15][16][17][18][19][20][21][22] focused on automatic or semiautomatic methods to output precisely optimized pathways.…”
Section: Introductionmentioning
confidence: 99%
“…It is the tedious and time consuming procedure to check whether trajectories contact an important organ/vessels or not. In order to address this problem, several research efforts on surgical path planning have been reported in the last decade, in particular for intracerebral hemorrhage (Seitel et al, 2011), epilepsy, deep brain stimulation (Bériault et al, 2012) (Essert et al, 2012) (Liu et al, 2012), hepatic surgery (Schumann et al, 2010) (Villard et al, 2003), and stereo electrode encephalography (Momi et al, 2013) (Zelmann et al, 2015). An important feature of these methods is that the optimal trajectories are obtained by minimizing the risk of passing through target region.…”
mentioning
confidence: 99%
“…To reduce the computing time, acceleration procedures utilizing graphics processing unit and data preprocessing, enabling interactive selection of trajectories, have been considered (Rincon-Nigro et al, 2014) (Shamir et al, 2012). Schumann et al (2010) proposed a rapid optimization process based on segmentation masks, but this approach has been limited to the case of a point target.…”
mentioning
confidence: 99%